Pengembangan Permainan Ludo Kimia sebagai Media Pembelajaran pada Materi Interaksi Antarpartikel - Iswendi Iswendi; Ririn Agustriana Iswara (Universitas Negeri Padang, 2020)
The purpose of this research was to develop Chemistry Ludo Game as a learning media on Intermolecular Attractions matter, determine level validity and practicality. This type of research are Research and development, using 4-D models. The instruments used a questionnaire of validity and practicality. The data was analysed using the Kappa Cohen formula. Validation was carried out by Chemistry lecturer FMIPA UNP and Chemistry teacher SMAN 3 Bukittinggi. Practicality was carried out by chemistry teachers and students of class X MIPA 3 SMAN 3 Bukittinggi. From the analysis of the data, validity and practicality are very high, the validity 0.83, the practicality of teachers 0.94 and students 0.86. These data shows that the developed Chemistry Ludo can be used as a learning media on interparticle interactions matter.